The Effect of Scientific Terms Error on Scientific Communication of Prospective Teachers and Progressive Education - Parmin Parmin; Stephani Diah Pamelasari; Sri Rahayu (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
The error of term usage in communication can be caused due to the misunderstanding of the words' mean-ing, or even the users might even realize their error but somehow keep using it deliberately. Thus, this study was conducted to find errors in using scientific terms in communication that influence the scientific communication of prospective science teachers. The research design used was mixed methods with sequen-tial explanatory strategies. The data were gathered through a closed questionnaire referring to the optional Likert Scale of 5 options and analyzed quantitatively. There were 256 participants or prospective science teachers as research subjects. The mean of the r count was 0.64, and the r table was 0.12. Therefore, it was judged as valid. The reliability test was obtained by Cronbach's Alpha of 0.951> 0.80. The results show that there were 13 errors of scientific terms performed by participants. Wilcoxon test obtained the Asymp value. Sig. of 0,000 <0.005 meaning that there were differences in the use of the term science in society and university. Representing and presenting were two aspects of scientific communication, with 40% obtain-ing moderate criteria. The research concludes that the scientific terms' error affects prospective teachers' sci-entific communication and progressive education since the errors have become a long habit. It must be over-come because the habit scientifically will also influence the trust of scientific truth.